The use of cartoon characters in brand advertising communications - G. V. Dovzhik; K. A. Arzhanova; V. N. Dovzhik (Цифровая социология)
The authors of the article explore how the cartoon characters are perceived in advertising products of famous brands among young people. To study this issue, focus groups were held, in which representatives of the youth audience took part. To demonstrate the stimulus material, 22 characters from animated films were selected (cartoons of the Soviet period, Disney studios cartoons and other foreign cartoons). For a large number of products, especially for children, the use of cartoon characters is logical and relevant in most cases. The level of popularity of Soviet cartoons is quite high, which gives brands the opportunity to use their characters in advertising communications. The most popular are the heroes of foreign cartoons (Disney studios and others). According to the results of the study, it was concluded that the use of cartoon characters in advertising communications of the brand contributes to its successful promotion, makes advertising bright and memorable, such advertising attracts the attention of the target audience and arouses its interest. At the same time, the authors point out that it is impossible to take the character out of the context of the cartoon, his image should be exactly the way people used to see him. In this case, advertising communication will be really successful. The results of the study can be used by brands when promoting goods and services using cartoon characters.